Coffee Shop Organizational Control Strategies for Improving Team Performance toward Customers: A Case Study of Talk Bogor (Oratio Directa, 2021)
The growth of coffee shops in Bogor creates competition that requires consistent team performance and customer-oriented service. This study examines the organizational control strategy used by Talk Bogor to improve team performance toward customers. It applies a post-positivist paradigm, a qualitative descriptive approach, and a case-study method. Data were collected through observation, interviews with the owner and relevant informants, and documentation, then checked through source triangulation. The analysis uses the organizational control framework associated with Philip Tompkins and George Cheney, covering simple, technical, bureaucratic, and concertive control. The findings indicate that Talk Bogor combines direct direction from the owner, operational use of digital media, service routines, and team dialogue. Two-way communication is used to discuss customer feedback, menu development, pricing, and service conditions. Concertive control is the most visible pattern because shared values and cooperation guide daily work. However, the evidence is limited to a single case and does not establish a causal increase in customer numbers.
Keywords: Organizational control; Team performance; Marketing communication; Coffee shop; Case study